Evaluasi Keamanan Autentikasi Pengguna pada Sistem Operasi Windows dan Linux - Galva Al Godzali; Rafif Isdarufa Athallah; Elkin Rivalni (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Authentication security is an important aspect of the operating system. This research evaluates the security of user authentication on Windows and Linux operating systems by analyzing various methods such as the use of passwords and two-factor authentication. This study compares effectiveness, flexibility, and stability to provide insight into their advantages and vulnerabilities. The literature review method is used by utilizing secondary data from relevant sources. The research results show that Linux offers superior security due to its open-source nature and strong permission-based model, while Windows excels in ease of use and integrated features such as Active Directory. These results aim to provide information to users and organizations in choosing an operating system that suits their needs.